Peran Manajemen SDM dalam Meningkatkan Produktivitas Karyawan di Era Digital - Rusli Rusli (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Abstract. This study aims to analyze the role of human resource management (HRM) in improving employee productivity in the digital era. The research employs a Systematic Literature Review (SLR) method by analyzing 15 relevant scientific articles published between 2020 and 2026, obtained from Google Scholar and SINTA databases. The findings indicate that HRM plays a strategic role as a strategic enabler in integrating digital technology with employee competency development. Practices such as e-recruitment, e-learning, Human Resource Information Systems (HRIS), and data-driven HR have been proven to enhance efficiency, effectiveness, and overall employee performance. However, the implementation of digital HRM still faces several challenges, including digital skill gaps, resistance to change, and limited organizational and technological readiness. Furthermore, the effectiveness of HRM is influenced by factors such as digital competence, adaptive organizational culture, transformational leadership, and the level of technology adoption. This study concludes that improving employee productivity in the digital era depends not only on the use of technology but also on the organization’s ability to manage human resources strategically and holistically. Keywords: human resource management, employee productivity, digital era, digital competence, digital transformation Abstrak. Penelitian ini bertujuan untuk menganalisis peran manajemen sumber daya manusia (SDM) dalam meningkatkan produktivitas karyawan di era digital. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan menganalisis 15 artikel ilmiah yang relevan dari tahun 2020–2026 yang diperoleh melalui Google Scholar dan SINTA. Hasil penelitian menunjukkan bahwa manajemen SDM memiliki peran strategis sebagai strategic enabler dalam mengintegrasikan teknologi digital dengan pengembangan kompetensi karyawan. Praktik seperti e-recruitment, e-learning, Human Resource Information System (HRIS), serta data-driven HR terbukti mampu meningkatkan efisiensi, efektivitas, dan kualitas kinerja karyawan. Namun, implementasi digitalisasi SDM masih menghadapi berbagai tantangan, seperti kesenjangan kompetensi digital, resistensi terhadap perubahan, serta keterbatasan kesiapan organisasi dan infrastruktur teknologi. Selain itu, efektivitas manajemen SDM dipengaruhi oleh faktor-faktor seperti kompetensi digital, budaya organisasi yang adaptif, kepemimpinan transformasional, dan tingkat adopsi teknologi. Penelitian ini menyimpulkan bahwa peningkatan produktivitas karyawan di era digital tidak hanya bergantung pada penggunaan teknologi, tetapi juga pada kemampuan organisasi dalam mengelola sumber daya manusia secara strategis dan holistik. Kata Kunci: Manajemen SDM, Produktivitas Paryawan, Era Digital, Kompetensi Digital, Transformasi Digital